Metode Sosiodrama untuk Meningkatkan Kemampuan Bahasa Arab Siswa Madrasah Aliyah - Ahmad Ismail (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2019)
Abstract The purpose of this article is to find out the differences in learning outcomes of students who use the sociodrama method and how big is the increase in Mahārah al-Kalām to students who apply the sociodrama method in Arabic learning that has some maharah as their basic competencies. This is an experimental study, where the research subjects are students of Madrasah Aliyah or Islamic high school. Two homogeneous groups were taken as samples; Class XI Religion 1 as an experimental class and Class XI Religion II as a control group. This research uses Randomized Pretest- Posttest Control Group Design as its research design. The results in this article are based on the results of statistical analysis which shows that the T- Posttest between the control and experimental groups shows that the value of T-count = -4.503 <T-table = 2.037 (Ha is accepted) which means that there are significant differences of the learning outcomes between the control group and the experimental group. Whereas the T-test of pretest and posttest of the experimental group resulted in a calculated T-value = 13,348 <T-table = 2,035 (Ha is accepted), which means that there was a significant increase in student learning outcomes in the experimental group. Keywords: Strategy, Sociodrama, Maharah Al-Kalām Abstrak Tujuan dari artikel ini adalah untuk mengetahui perbedaan hasil belajar siswa yang menggunakan metode sosiodrama dan seberapa besar peningkatan Mahārah al-Kalām pada siswa yang menerapkan metode sosiodrama dalam pembelajaran bahasa Arab yang mempunyai beberapa maharah sebagai kompetensi dasarnya. Penelitian ini merupakan penelitian eksperimen, dimana subjek penelitiannya adalah siswa Madrasah Aliyah. Dari populasi di sekolah yang diteliti diambil dua kelompok homogen sebagai sampelnya, yaitu kelas XI Agama 1 sebagai kelas eksperimen dan kelas XI Agama II sebagai kelompok kontrol. Penelitian ini menggunakan Randomized Pretest- Posttest Control Group Design sebagai desain penelitiannya. Hasil penelitian dalam artikel ini didasarkan pada hasil analisis statistik yang menunjukkan bahwa uji T- Posttest antara kelompok kontrol dan eksperimen didapatkan nilai T-hitung = -4,503 < T-tabel = 2,037 (Ha diterima) yang artinya terdapat perbedaan yang signifikan hasil belajar antara kelompok kontrol dengan kelompok eksperimen. Sedangkan uji-T nilai pretest dan posttest kelompok eksperimen menghasilkan nilai T-hitung = 13,348 < T-tabel = 2,035 (Ha diterima), yang artinya terdapat peningkatan yang signifikan pada hasil belajar siswa kelompok eksperimen. Kata Kunci: Strategi, Sosiodrama, Maharah Al-Kalām